M. G. Müller, Die Teilungen Polens 1772 - 1793 - 1795 - Salmonowicz, Stanisław (Czasopismo Prawno-Historyczne, 1986)
Recenzja: Michael G. Müller, Die Teilungen Polens 1772-1793-1795, München 1984, ss. 133.